2014
DOI: 10.1111/emr.12136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire on vegetation and arthropods in a coastal heath, south‐east Queensland

Abstract: Summary Fire is an important part of many Australian ecosystems, and determining how it affects different vegetation communities and associated fauna is of particular interest to land managers. Here, we report on a study that used sites established during a 39‐year fire experiment in coastal heathland in southeastern Queensland to compare arthropod abundance and vegetation in 1.5–2.6 ha sites that were (i) long unburnt, (ii) burnt every 5 years and (iii) burnt every 3 years. We found that the abundance of ants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…While frequent burning favoured facultative resprouting species across all ecosystems, in the heathland, obligate seeder species density was highest in the 3YR treatment, followed by the 5YR and was lowest in the IB. This is consistent with previous studies which suggest long unburnt periods (>12 years) can be detrimental to seed regenerating species in heathland ecosystems but contradicts existing understanding that frequent fire will result in declines in the abundance of obligate seeders (Foster et al, 2018; Manwaring et al, 2015; McFarland, 1988). Similarly, the woodland showed a trend (although not statistically significant) towards higher obligate seeder density in 5YR, followed by 3YR and IB.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While frequent burning favoured facultative resprouting species across all ecosystems, in the heathland, obligate seeder species density was highest in the 3YR treatment, followed by the 5YR and was lowest in the IB. This is consistent with previous studies which suggest long unburnt periods (>12 years) can be detrimental to seed regenerating species in heathland ecosystems but contradicts existing understanding that frequent fire will result in declines in the abundance of obligate seeders (Foster et al, 2018; Manwaring et al, 2015; McFarland, 1988). Similarly, the woodland showed a trend (although not statistically significant) towards higher obligate seeder density in 5YR, followed by 3YR and IB.…”
Section: Discussionsupporting
confidence: 89%
“…There has been little research investigating the long-term effects of contrasting fire frequencies in these subcoastal ecosystems. McFarland (1988) showed that the structure and vegetation composition in heathlands of Cooloola National Park (Great Sandy Biosphere) changed with varying time since the last fire, while Manwaring et al (2015) investigated invertebrate abundance and some effects on vegetation. No prior research has comprehensively analysed the responses of understorey vegetation and topsoil carbon (C) and nitrogen (N) to regular long-term burning or fire omission at the study sites.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Eliott (2015) explored the use of Cerambycid beetles as bioindicators in Bauple State Forest. In heathland at Cooloola, Manwaring et al (2015) compared the abundance of invertebrates (with a focus on ants) between a long unburnt site and sites that had been burnt at three and five year intervals.…”
Section: Australian Zoologist Volume 39 (4)mentioning
confidence: 99%
“…; Manwaring et al . ), and no studies in naturally occurring subtropical eucalypt forests. There has been a limited amount of research undertaken on the impacts of fire regime on cerambycid beetles internationally (e.g.…”
Section: Introductionmentioning
confidence: 99%